Physiological and Pathophysiological Relevance of the Anion Transporter Slc26a9 in Multiple Organs - Liu, Xuemei; Li, Taolang; Tuo, Biguang (Frontiers in Physiology, 2018)
Transepithelial Cl- and HCO3- transport is crucial for the function of all epithelia, and HCO3- is a biological buffer that maintains acid-base homeostasis. In most epithelia, a series of Cl-/HCO3- exchangers and Cl- channels that mediate Cl- absorption and HCO3- secretion have been detected in the luminal and basolateral membranes. Slc26a9 belongs to the solute carrier 26 (Slc26) family of anion transporters expressed in the epithelia of multiple organs. This review summarizes the expression pattern and functional diversity of Slc26a9 in different systems based on all investigations performed thus far. Furthermore, the physical and functional interactions between Slc26a9 and cystic fibrosis transmembrane conductance regulator (CFTR) are discussed due to their overlapping expression pattern in multiple organs. Finally, we focus on the relationship between slc26a9 mutations and disease onset. An understanding of the physiological and pathophysiological relevance of Slc26a9 in multiple organs offers new possibilities for disease therapy.